Measurement of concrete E-modulus evolution since casting: A novel method based on ambient vibration - Miguel Azenha (2010)
The use of ambient vibration tests to characterize the evolution of E-modulus of concrete right after casting is investigated in this paper. A new methodology is proposed, which starts by casting a concrete cylindrical beam inside a hollow acrylic formwork. This beam is then placed horizontally, simply supported at both extremities, and vertical accelerations resulting from ambient vibration are measured at mid-span. Processing these mid-span acceleration time series using power spectral density functions allows a continuous identification of the first flexural frequency of vibration of the composite beam, which in turn is correlated with the evolutive E-modulus of concrete since casting. Together with experiments conducted with the proposed methodology, a complementary validation campaign for concrete E-modulus determination was undertaken by static loading tests performed on the composite beam, as well as by standard compressive tests of concrete cylinders of the same batch loaded at different ages.